Development and validation of the Early Executive Functions Questionnaire: A carer‐administered measure of Executive Functions suitable for 9‐ to 30‐month‐olds. (21st August 2021) - Hendry, Alexandra; Holmboe, Karla
Abstract: Executive functions (EFs) enable us to control our attention and behavior in order to set and work toward goals. Strong EF skills are linked to better academic performance, and greater health, wealth, and happiness in later life. Research into EF development has been hampered by a lack of scalable measures suitable for infancy through to toddlerhood. The 31‐item Early Executive Functions Questionnaire (EEFQ) complements temperament measures by targeting cognitive and regulatory capabilities. Exploratory Factor Analysis ( n  = 486 8‐ to 30‐month‐olds) and Confirmatory Factor Analysis ( n  = 317 9‐ to 30‐month‐olds) indicate Inhibitory Control, Flexibility, and Working Memory items load onto a common "Cognitive Executive Function (CEF)" factor, while Regulation items do not. The CEF factor shows strong factorial measurement invariance for sex, and partial strong factorial measurement invariance for age. CEF and Regulation scores show limited floor and ceiling effects, good internal consistency, short‐term stability, and convergent validity with carer‐report measures of attentional control. The EEFQ is sensitive to developmental change. Results indicate that the widely overlooked period between late infancy and early toddlerhood may be a sensitive period for EF development. The low‐resource demands of the EEFQ afford the possibility to study emergent EFs at scale; opening up new opportunities in basic developmental and intervention research.